Dobór wskaźników ekonomiczno-finansowych do badań porównawczych efektywności krajowych spółek dystrybucji energii elektrycznej - Chrabołowska, Joanna (Selection of Economic-Financial Indices for Comparative Studies of Effectiveness of Polish Electrical Energy Distribution Utilities, 2005)
The article presents selection process of economic-financial indices for comparative studies of effectiveness of domestic electrical energy distribution utilities. There have been analysed 42 economic-financial indices related to distribution and transmission activity of 33 distribution utilities. An accessible set of indices has been reduced essentially and statistically. On the basis on factor analysis there have been described 3 dimensions (profitability and productivity, employment effectiveness and operational efficiency) that make full characteristics of examined distribution utilities possible. The companies have been ranked according to each of above-mentioned dimensions. In author's opinion multivariate approach to the assessment of efficiency is indispensable.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 151-161